O ativismo judicial e suas dimensões na atuação do supremo tribunal federal : uma análise sob o prisma da separação dos poderes e da judicialização. - Buzatto, Gustavo (2017)
In the last few decades, mostly because of the re-democratization of the country and the new constitutional order instituted with the promulgation of the 1988 Federal Constitution, the Brazilian judiciary has been experimenting an unprecedented rise. The judicialization phenomenon and the submission of themes of - besides juridical -political and social natures, have brought to the jurisdictional area subjects that initially enconmpass the territory of political action of the other branches, and that, in the name of the principle of non-obviation of Judiciary jurisdiction, are faced by the judiciary, which, in order to remedy the omission or the insufficiency or incapacity of administrative or legislative action, pronounces the jurisdictional provision that ends up entailing reflexes on these state functions. The more broad and proactive activity creates the debate and questioning about the legitimacy of the jurisdictional conduct that ends up interfering in the other branches typical sphere of activity, meaning that it could violate the separation of po wers and the democratic system or be a manifestation of the harmonical practice among the state functions and promotion of the democratic ideals. The judicial activism, which presents a controversial definition inside the doctrine, is a phenomenon in which this broad and intense action of the jurisdictional organs has been accommodated, specially the Supreme Court's, which, before relevant decided cases, has evidenced its several activist dimensions. A mere passive enforcer of laws judiciary cannot be conceived anymore, but how much can it go on in its interpretative, creative and precepts, values and constitutional purposesmaker intent is what is questioned. If the notion about the activism is the one of a violating acting, finding a new concept is imposed, in which this broadening activity of the Brazilian judiciary is legitimately accommodated.